2023
DOI: 10.1186/s12962-023-00475-3
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of robot-assisted gait training in patients with bilateral spastic cerebral palsy

Stanislava Klobucká,
Robert Klobucký,
Katarína Valovičová
et al.

Abstract: Background To date, there have been no published studies evaluating the cost-effectiveness of robot-assisted gait training (RAGT) in adolescent and adult patients with cerebral palsy (CP). The study´s aim was to analyse the cost-effectiveness of RAGT versus conventional kinesiotherapy (CON) from the health care provider’s perspective. Methods We expressed the cost-effectiveness of RAGT in the Lokomat® system after analysing the costs and effects of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…These reviews suggested that rehabilitation technologies (RT) can be effective in improving clinical outcomes and reducing healthcare costs for people with physical disabilities. In recent years, there has been growing interest in the cost-effectiveness of digital technologies, particularly virtual reality (VR) tools and video games, as well as robotic technologies in the field of motor rehabilitation [ 9 , 21 , 31 ]. This systematic review aimed to synthesize the most recent evidence on the cost-effectiveness of digital motor rehabilitation technologies compared to conventional care, considering the latest studies and methodological guidelines for economic evaluations, in order to inform decision-making regarding the adoption of these often-costly technologies in routine rehabilitation care.…”
Section: Introductionmentioning
confidence: 99%
“…These reviews suggested that rehabilitation technologies (RT) can be effective in improving clinical outcomes and reducing healthcare costs for people with physical disabilities. In recent years, there has been growing interest in the cost-effectiveness of digital technologies, particularly virtual reality (VR) tools and video games, as well as robotic technologies in the field of motor rehabilitation [ 9 , 21 , 31 ]. This systematic review aimed to synthesize the most recent evidence on the cost-effectiveness of digital motor rehabilitation technologies compared to conventional care, considering the latest studies and methodological guidelines for economic evaluations, in order to inform decision-making regarding the adoption of these often-costly technologies in routine rehabilitation care.…”
Section: Introductionmentioning
confidence: 99%